STRATEGI MANAJEMEN KONTROL BI’AH ARABIAH DI PP DARUL LUGHAH WADDIRASATIL ILMIYAH PAMEKASAN - M. Anas Hidayat; Nuril Mufidah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
Islamic boarding school is one of the unified educational built on the concept of Islamic culture, which includes learning Arabic called Bi'ah Arabiyah as its implication process, with the emphasis being centering on the aspect of creating and forming learning strategies based on the Arabic language environment through interaction and communication for students. The purpose behind this research is to find out the control management strategy applied in Darul Lughah Islamic Boarding School Waddirasatil Ilmiyah Pamekasan. By taking the location in the Darul Lughah Waddirasatil Ilmiyah Pamekasan Islamic Boarding School area, this research in its preparation process was categorizing as descriptive qualitative research with a series of stages of collecting data sources using study, observation, and interview methods. The data analysis technique applied by the researcher are data reduction, data presentation, and data verification. The findings of this study is the form of Bi'ah Arabiyah control management strategy carried out at the Darul Lughah Waddirasatil Ilmiyah Pamekasan Islamic Boarding School that classified using two different language environments, namely formal Bi'ah Arabiyah which puts the focus on mastering the grammatical rules of the language and the informal Bi'ah Arabiyah which makes the environment outside the classroom a place where students practice their Arabic language skills in the community where the two activities are combined by work programs related to linguistics such as Sima'i wal Tarjamah and Tazwidul Mufradat.